УЧЕНИЕ МУЗЫКАЛЬНОЙ ТЕОРИИ ВОСТОКА АБУ НАСРA ал-ФAРAБИЙ и АБУ АЛИ ИБН СИНA (Авицина-медицина) - Саидий Саид Болта-Зода (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The article tells about 12 rhythmic designations of music theory by Abu Nasr al-Farabi and Abu Ali ibn Sina as the great founders of the East.